Total synthesis of (−)-aritasone via the ultra-high pressure hetero-Diels–Alder dimerisation of (−)-pinocarvone - Uroos, Maliha; Pitt, Phillip; Harwood, Laurence; Lewis, William; Blake, Alexander J.; Hayes, Christopher J. (Royal Society of Chemistry, 2017)
This paper describes a total synthesis of the terpene-derived natural product aritasone via the hetero-Diels-Alder [4+2] cyclodimerisation of pinocarvove, which represents the proposed biosyntheic route. The hetero-Diels-Alder dimerisation of pinocarvone did not proceed under standard conditions, and ultra-high pressure (19.9 kbar) was required. As it seems unlikely that these ultra-high pressures are accessible within a plant cell, we suggest that the original biosynthetic hypothesis be reconsidered, and alternatives are discussed.